ChemInform Abstract: Direct Synthesis of 5‐ and 6‐Substituted 2‐Aminopyrimidines as Potential Non‐natural Nucleobase Analogues. Issue 48 (2nd December 2014) - Radhakrishnan, K.; Sharma, Namita; Kundu, Lal Mohan
Abstract 15 Isocytosines of type (III) and (V) are prepared under microwave irradiation under solventless conditions.